A survey on recent approaches of electromagnetic absorption reduction with respect to human head exposure to GSM frequency bands - O. Mumin, Abdulrashid; Abdulhasan, Raed Abdulkareem; Alias, Rozlan; A. Awaleh, Abdisamad; Abdullah, Jiwa; Dahlan, Samsul Haimi (Science International, 2017)
The cellular phone usage has been growing dramatically over the last decade and became a crucial part of our life. One of the key components of mobile phone is the antenna that receives and transmits electromagnetic (EM) energy. The safety of human head exposure of electromagnetic (EM) waves emitted from cell phones has attracted public concern. A comprehensive review of recent approaches and techniques of electromagnetic absorption reduction over GSM bands are presented in this paper. Protection attachments between the antenna and the human head were proposed by many researchers. These distinct techniques have been classified in to 4 categories including the use of ferrite sheet, perfect electric conductor (PEC), electromagnetic band gap (EBG) structure and metamaterials. Few good papers were reviewed and evaluated in each group for proof of concept. Finally, a comparison between these techniques was done.